OPTIMIZING CARBON EMISSIONS AND COST IN VACCINE TRANSPORTATION: DESIGNING A TYPE-2 FUZZY ENVIRONMENT MODEL FOR EFFECTIVE VACCINE DISTRIBUTION - Bhakuni, Pooja; Das, Amrit (International Journal of Industrial Engineering: Theory, Applications and Practice, 2023)
Vaccination represents one of the crowning achievements of world health. Contagious illness infestations can be controlled with the use of vaccines. During a virus outbreak, decision-making has high constraints on time and resources, and an efficacious mathematical model for vaccine transportation can assist healthcare planning organizations. The objective of this research work is to minimize the overall carbon emission, cost, and distance covered during transportation. Cost assessment and optimization are essential for the allocation of adequate monetary funds for vaccination plans. Due to non-uniform infrastructure and diverse topography, impreciseness arises thus to capture uncertainty in environment emission, cost, demand, and carbon cap parameters are regarded as gamma type-2 fuzzy variables. Chance constraint programming is employed using the critical value reduction method for the crisp conversion of fuzzy problems to crisp form. The proposed optimization-based framework is applied through a case study from the state of Uttarakhand in India.